Discrete Multilinear Spherical Averages. Issue 2 (9th January 2019) - Cook, Brian
Abstract: In this note we give a characterization of ^p× … × ^p→ ^q boundedness of maximal operators associated with multilinear convolution averages over spheres in Z^n .